Physicochemical parameters of chicken drumstick and breast cuts raised in free-range and conventional systems: Comparative interpretation in the 2024-2025 context (Research, Society and Development, 2025)
This study aimed to characterize the physicochemical parameters of chicken drumstick and breast cuts from conventional and free-range production systems, reinterpreting original laboratory data in light of technological and regulatory updates from 2024–2025. Moisture, lipid, protein and ash contents were evaluated on a wet basis using official methodologies from the Ministry of Agriculture and current ISO standards. Original results indicated moisture levels between 73.03% and 76.41%, lipids between 0.45% and 2.63%, proteins ranging from 20.09% to 26.81%, and ash contents from 0.98% to 1.52%, all compliant with current Brazilian legislation. Comparative analysis indicates that, despite significant production advances in poultry farming between 2020 and 2025 — including improvements in animal welfare, biosafety, nutrition and traceability — physicochemical parameters of chicken meat have remained stable. It is concluded that differences between anatomical cuts remain more relevant than differences between production systems, demonstrating consistency and robustness of the original data within the contemporary scenario.